Rhodomyrtone decreases Staphylococcus aureus SigB activity during exponentially growing phase and inhibits haemolytic activity within membrane vesicles. (March 2019) - ,; Jover, A.; Barcenilla, F.; García, M.; Pujol, M.; Gasch, O.; Domínguez, M.A.; Camoez, M.; Dueñas, C.; Ojeda, E.; Martínez, J.A.; Marco, F.; et al.
Abstract: Sigma factor B (SigB) controls the expression of Staphylococcus aureus genes including virulence factors and plays a role in the bacterial secretion system through membrane vesicle production. Inhibition of SigB could attenuate SigB dependent virulence and secretion system. The objective of this study was to determine the effects of rhodomyrtone on SigB and virulence factors related to SigB. Minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) values of rhodomyrtone against 67 clinical methicillin-resistant S. aureus isolates were 0.25–8 μg/ml, which were similar to those of vancomycin. Using luciferase gene fused to SigB dependent promoters of asp23, five time reduction in SigB activity was observed when the bacteria were treated with rhodomyrtone for 3 h. Rhodomyrtone significantly reduced SigB activity in a concentration dependent manner in exponentially growing cells ( P < 0.05). In addition, sigB mutant was more sensitive towards increasing concentrations of rhodomyrtone than the wild type and yabJ-spoVG mutant. Rhodomyrtone at 0.625 μg/ml reduced the growth of sigB mutant by approximately 99%, compared with the yabJ-spoVG mutant and the wild type. Membrane vesicles were significantly reduced in the bacterial cells when treated with 0.5 × MIC rhodomyrtone ( P < 0.05). Decreased haemolytic activity was detected within rhodomyrtone-treated membrane vesicles. The results indicated that rhodomyrtone inhibited S. aureus SigB activity during exponentially growing phase and inhibited haemolytic activity within membrane vesicles.